Fire distinguishers: Refined interpretations of polycyclic aromatic hydrocarbons for paleo-applications - Karp, A.T.; Holman, Alex; Hopper, Peter; Grice, Kliti; Freeman, K.H. (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Polycyclic aromatic hydrocarbons (PAHs), produced via incomplete combustion of organics, convey signatures of vegetation burned in the geologic past. New and published burn experiments reveal how the quantity, distributions, and isotopic abundances of fire-derived PAHs were influenced by fuel types, burn conditions, and also phase. PAH concentrations were higher in burn residues from moderate burn temperatures (400–500 °C), and significantly lower in residues from cooler (<300 °C) or hotter (>600 °C) conditions, especially when oxygen was limited. PAH forms tended to be smaller in smoke samples and larger in residues, consistent with molecular physical and chemical properties. Plant functional types were distinguished by relative amounts of retene and dimethyl phenanthrene isomers. Isotopically distinct photosynthetic pathways of the burned material were reflected in the δ13C values of PAHs, which faithfully captured biomass signatures as well as the ∼12‰ offset between C3 and C4 plant types. PAH size, alkylation, and isotope characteristics can differentiate combusted plant types and distinguish between air-borne and sedimentary transport mechanisms. New proxy approaches using PAH amounts, distributions, and isotope signatures can aid and refine interpretations of paleofire ecology in the geologic record.